Experimental study on the shear failure of layered rock bridges - Yu, Jianxin; Zhou, Zhibin; Liu, Huanchun; Zhou, Lianhao; Li, Zhenzhen; Cheng, Long (Frontiers in Earth Science, 2023)
The structural face of rock plays a decisive role in the stability of geotechnical engineering, and the mechanism of damage destabilization of layered rock masses is still unclear. By preparing rock-like materials, shear damage tests on layered rock masses were carried out under different bedding dip angles, different bridge widths, different normal forces, and forward and reverse shear effects. With the increase in the bridge width, the influence of the joint inclination angle on the shear damage process of the rock sample decreases; the peak shear strength of the specimen is the largest when the joint inclination angle is 60°, followed by 90°, 30°and 0°from large to small; the damage mode in forward shear is mainly tensile damage, and the damage mode in reversed shear is mainly shear damage; the peak number of acoustic emission events is proportional to the joint inclination angle and the bridge width of the specimen, and the number of acoustic emission events is proportional to the joint inclination angle and the bridge width of the specimen. The number of acoustic emission peak events is proportional to the bedding angle of the sample and the width of the rock bridge. The peak number of acoustic emission events in the reverse shear of the layered rock mass is greater than that in the forward shear. The results of this study provide a basis for identifying the mechanism of shear damage in layered rock masses.